A Novel PVT Model Incorporating Mass Transfer Rate for Subsurface Data Determination - Review - Hon , Vai Yee (2008)
In field development and reservoir surveillance planning, there is an absolute need to obtain reliable values for reservoir pressures, productivity indexes and other values on a continuous basis so that planning can be done reliably and production / recovery can be optimized. However, continuous data acquisition is often where we stumbled due to a combination of economic, operational/logistical constraints. An alternative is to derive these key parameters from surface data using dynamic well modeling techniques. Subsurface data acquisition will be replaced by surface data acquisition, reducing the number of well interventions and data acquisition costs.